“Amor à vida” project: evaluation of the results with health, educaction and social assistance professionals from Jaguaribe – Ceará - Virgínia Maria Costa de Oliveira (Rev Rene)
We evaluated the results of the “Amor à Vida” Project in the city of Jaguaribe – Ceará, because it has been announced as an inductor for implanting the adolescent health policy, focusing on health promotion. Objectives: to evaluate the results of the “Amor à Vida” Project with health, education and social assistance to professionals, after eight years of implantation, observing if its practices show clearly the central health promotion principles; trace the profile of the professionals that participate on the project; investigate the professionals adhesion to the objectives and methodology proposed by the project and identify, among the professionals activities, the strategies adopted to articulate intersectorial actions. Scenery of the study: 02 middle level schools, 03 basic health units and 01 psychosocial assistance center. The population of the study was: 14 teachers, 03 school administrators, 03 doctors, 03 nurses, 02 nurse auxiliaries and 01 social assistant.